2000
DOI: 10.1677/jme.0.0240253
|View full text |Cite
|
Sign up to set email alerts
|

Androgen ablation results in differential regulation of transforming growth factor-beta isoforms in rat male accessory sex organs and epididymis

Abstract: The male accessory sex organs and epididymis regress following androgen depletion, although the onset of apoptosis varies temporally depending upon the tissue type. Transforming growth factor-1 (TGF-1) is an androgen-repressed gene and believed to be an apoptotic agent in the regressing rat ventral prostate (VP). Hence, in order to investigate the status of TGF-isoforms following castration in androgen-dependent tissues other than VP, this study was undertaken. Northern blot analysis using total RNA from these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Differential expression profiles for TGF-b isoforms (TGF-b1, TGF-b2, and TGF-b3) have previously been characterized in the rat epididymis by northern blot (Desai et al 1998, Desai & Kondaiah 2000. In these studies, substantial TGF-b1 expression was observed compared with other isoforms; TGF-b1 expression was upregulated in the caput, corpus, and cauda epididymides following total androgen ablation by orchidectomy.…”
Section: Growth Factor Systems In the Epididymismentioning
confidence: 99%
“…Differential expression profiles for TGF-b isoforms (TGF-b1, TGF-b2, and TGF-b3) have previously been characterized in the rat epididymis by northern blot (Desai et al 1998, Desai & Kondaiah 2000. In these studies, substantial TGF-b1 expression was observed compared with other isoforms; TGF-b1 expression was upregulated in the caput, corpus, and cauda epididymides following total androgen ablation by orchidectomy.…”
Section: Growth Factor Systems In the Epididymismentioning
confidence: 99%
“…(36) Furthermore, androgen ablation is found to induce expression of each of the three TGFb isoforms in an isoform-and tissue-specific manner in the seminal vesicle and epididymis. (37) Whole organ culture of neonatal seminal vesicles with TGFb1 inhibits androgen-induced epithelial branching and suppresses protein and mRNA synthesis; however, TGFb1 does not affect seminal vesicle growth in the absence of androgens. (38) Interest in the role of TGFb in the prostate stems from its likely involvement in prostate cancer.…”
Section: Testis Function and Spermatogenesismentioning
confidence: 99%
“…On the other hand, testosterone administration to intact or castrated rats results in benign and/or atypical prostatic hyperplasia (Colombel and Buttyan 1995). Testosterone regulates the expression of various growth factors and their receptors, including epidermal growth factor (EGF) and EGF receptor, transforming growth factors (TGFs), TGF-α, TGF-β1, TGF-β2, and TGF-β3 and TGF-β type II receptor, basic fibroblast growth factor (bFGF) and FGF receptor I, hepatocyte growth factor (HGF), and HGF receptor, keratinocyte growth factor (KGF) and vascular endothelial growth factor (VEGF) in the rat prostate Hägg-ström et al 1999;Desai and Kondaiah 2000).…”
Section: Introductionmentioning
confidence: 99%